2015
DOI: 10.1039/c5cy00737b
|View full text |Cite
|
Sign up to set email alerts
|

Catalysts for the selective catalytic reduction of NOx with NH3 at low temperature

Abstract: ARTICLE This journal isSelective catalytic reduction of NOx with NH3 (NH3-SCR) at low temperature is a major challenge in environmental catalysis. In recent years, great efforts have been applied to the development of low-temperature SCR catalysts for both stationary sources and diesel engines. Mn-based catalysts have attracted great attentions due to their excellent low-temperature activity. However, vulnerability to SO2 and H2O poisoning and preference for N2O formation make these catalysts still far away fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
95
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(100 citation statements)
references
References 137 publications
2
95
0
3
Order By: Relevance
“…High Ce 3+ ion concentration contributed to the high amount of chemisorbed oxygen, which increased the redox cycle and enhanced the reducibility of hydrogen. This is because the Ce 3+ ions will assist the migration of O 2 from gas phase to the surface of the catalyst [8,23]. Afterwards, Wei et al [24] explained that NO x removal using FeCu/zeolite catalyst followed both Eley–Rideal and Langmuir–Hinshelwood mechanisms.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…High Ce 3+ ion concentration contributed to the high amount of chemisorbed oxygen, which increased the redox cycle and enhanced the reducibility of hydrogen. This is because the Ce 3+ ions will assist the migration of O 2 from gas phase to the surface of the catalyst [8,23]. Afterwards, Wei et al [24] explained that NO x removal using FeCu/zeolite catalyst followed both Eley–Rideal and Langmuir–Hinshelwood mechanisms.…”
Section: Reviewmentioning
confidence: 99%
“…However, some problems are still evident with the use of this catalyst, e.g., the vanadium species is highly toxic to humans and the environment, and excessive dust pollution will usually result from the upstream flue gas, which can cause the deactivation of the catalyst. In addition, the catalyst also has a limited temperature window (300–400 °C) and poor thermal stability [78]. Hence, there is an urgent need to find other catalysts that can overcome these drawbacks and also have high resistance to water (H 2 O) and oxidation of SO 2 to SO 3 , so that high activity and selectivity, high thermal stability, and a temperature lower than 300 °C can be achieved, thus increasing the lifetime of the catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…As well known, the commercial catalysts (V 2 O 5 -WO 3 (or MoO 3 )/TiO 2 ) used in thermal power plant are in the monolithic form because the honeycomb monoliths are suitable for a high gas flow rate, reduce pressure drop problems, exhibit high tolerance to dust and attrition, and are easy to regenerate [103][104][105][106]. Recently, metal foam and wire mesh as novel monolithic support for Mn-based and other vanadium-free SCR catalysts are drawing an increasing amount of attention due to their high porosity, stability, thermal conductivity, and mass transfer ability [107,108].…”
Section: Monolithic Catalystsmentioning
confidence: 99%
“…Among them, NH 3 -SCR is the most common technology for deep removal of NO x from various kinds of flue gas. In this process, the NO x in flue gas selectively reacts with gaseous ammonia over the catalyst to produce nitrogen and water without generating any secondary pollutants [5][6][7]. Currently, the global demand for SCR systems is increasing rapidly and China has the biggest market.…”
Section: Introductionmentioning
confidence: 99%
“…% silica introduced in catalyst molding [10,12]. Many reports in the literature [5,[16][17][18] have reported that TiO 2 -SiO 2 support can improve catalytic activity and SO 2 durability. Such superior low-temperature SCR activity was mainly attributed to the presence of polymeric vanadate species and high redox properties besides high surface area.…”
Section: Introductionmentioning
confidence: 99%